Malnutrition among children with cerebral palsy in Hospital Raja Perempuan Zainab II and Hospital Universiti Sains Malaysia - Ismail, Nor Diyana (2018)
Introduction: Poor nutrition is often reported as a problem among children with cerebral palsy. They are more vulnerable than any other normal children because of their physical disabilities, impairments and inadequate capacity to achieve normal function therefore needing higher nutritional requirements for optimum growth and development. Objectives: This study aimed to provide data on prevalence of malnutrition among children with cerebral palsy in HRPZ II and HUSM and to determine the associated factors of malnutrition. Methods: A cross sectional study is performed among children with cerebral palsy aged 2 to 18 years old attending the paediatric neurology and rehabilitation clinics in Hospital USM and Hospital Raja Perempuan Zainab II (HRPZ II) from June to November 2017. Interviews were done and case notes were reviewed to determine the demographic characteristics, medical problems, feeding behaviour and clinical assessments. Simple and multiple logistic regression analysis were used to identify the factors associated with malnutrition. Results: A total of 141 patients were enrolled and 62.4% (male = 84, female = 57) of children with cerebral palsy were severely malnourished, with stunting being the most common category, followed by underweight and thinness. Severe malnutrition is more prevalent in patients with severe motor impairments, having feeding difficulties and comorbidities. The main factor for severe malnutrition is spastic quadriplegia having 5 to 20 times the odds of being severely malnourished compared to other types of CP with or without having feeding difficulties. Conclusion: Prevalence of severe malnutrition is high in children with CP especially among children with spastic quadriplegia, thus showing the need for improvement in appropriate nutritional intervention for this group of patients.